Scaling Up Innovative Participatory Design for Public Transportation Planning: Lessons from Experiments in the Global South. Issue 12 (December 2020) - Zegras, Chris; Leape, Jonathan; Carrasco, Juan Antonio; Navas, Cristian; Venter, Christo; Vergel-Tovar, Erik
New data, new technologies, and greater computational power are changing the possibilities for involving stakeholders in transportation planning. This article explores these possibilities by comparing deployments of an interactive web-based public transportation mapping system in four cities of the Global South. Structured workshops focused on different public transportation improvement projects and involved different types of stakeholders. Despite the differences across the workshops, they allow for some comparison of the effects. In relation to the technology itself, participants broadly agreed about its usefulness and usability. Pre-/post-workshop surveys suggest that participants learned about the transportation projects presented but reveal modest evidence in relation to other impacts, such as learning about the concept of accessibility, and gaining an appreciation for the potential broader urban system impacts of public transport projects. Knowledge among the participants tended to converge, and the tool helped promote dialog among participants and generated some empathy for others. The workshop experiences provide some hope for such tools in enhancing public transportation planning processes, globally, but "scaling up" the technology would need to overcome institutional, technical, and procedural challenges.